Dictogloss and the production of the English third person '–s' by CLIL and mainstream EFL learners: A comparative study - Basterrechea, María; García Mayo, María del Pilar (International Journal of English Studies, 2014)
This study compares focus on form in Content and Language Integrated Learning (CLIL) and mainstream English as a Foreign Language (EFL) contexts in the production of a specific morphological feature, the English 3rd person singular present tense marker –s. Research conducted in CLIL contexts to date examining morphosyntactic features has yielded disparate results. Thus, little is known about how this methodology affects learners’ attention to form while completing a dictogloss task (Wajnryb, 1990). In the study 116 adolescent learners (CLIL, n = 54; mainstream EFL, n= 62) in the Basque Autonomous Community completed a dictogloss collaboratively and individually. Results showed that CLIL learners noticed and produced more instances of the 3rd person singular -s than mainstream learners, but not in a significant manner, and that those working in pairs in the CLIL group obtained significantly better results.